Targeting ferroptosis, pyroptosis and necroptosis for cancer immunotherapy in melanoma: mechanistic insights and clinical perspectives - Shan, Zexing; Liu, Fei (Frontiers in Immunology, 2025)
Melanoma, an aggressive malignancy originating from melanocytes, is characterized by rapid metastasis and dismal prognosis in advanced stages, with a 5-year survival rate of only 16% for stage IV disease. Despite breakthroughs in immune checkpoint inhibitors (ICIs) targeting CTLA-4 and PD-1/PD-L1, therapeutic challenges persist, including heterogeneous response rates, acquired resistance, and immune-related toxicities, underscoring the need for strategies to augment immunogenicity and overcome immune evasion. Programmed cell death (PCD) pathways—ferroptosis, pyroptosis, and necroptosis—have emerged as critical regulators of antitumor immunity. Ferroptosis, driven by iron-dependent lipid peroxidation (LPO), enhances immunogenicity through damage-associated molecular pattern (DAMP) release and depletion of immunosuppressive cells. Pyroptosis, mediated by gasdermin (GSDM) pore formation, promotes CD8+ T cell infiltration via pro-inflammatory cytokine secretion, while necroptosis, governed by Receptor-Interacting Protein Kinase 1 (RIPK1)/RIPK3-MLKL signaling, facilitates antigen cross-presentation and adaptive immune memory. In melanoma, dysregulation of these pathways contributes to tumor progression and immunosuppression, yet their targeted activation reshapes the tumor microenvironment (TME) to synergize with ICIs. Current challenges, including metabolic plasticity and off-target effects, highlight the necessity for precision approaches. This review delineates the mechanistic interplay of ferroptosis, pyroptosis, and necroptosis in melanoma immunotherapy, emphasizing advances in pharmacological induction, nanotechnology-driven delivery systems, and rational combination with ICIs. By integrating preclinical insights and clinical perspectives, we propose that co-targeting these immunogenic cell death (ICD) pathways offers a transformative strategy to enhance therapeutic efficacy, circumvent resistance, and achieve durable remission in melanoma.